'For whom the sovereignist Bell Tolls?' Individual determinants of support for sovereignism in ten European countries. Issue 2 (14th March 2020) - Basile, Linda; Borri, Rossella; Verzichelli, Luca
ABSTRACT: Sovereignism and populism are increasingly making headlines, but their nature and definition still remain controversial. Moreover, while literature has often treated the two concepts separately, they are increasingly associated in the current representations and narratives of political events. In this paper, we argue that sovereignism is one of the recurrent and core themes of populism, and pre-exists it. We conceive of sovereignism as a multidimensional concept, based upon a three-fold space, identifying its political, cultural, and economic expressions. By using survey data, we first empirically assess the existence of these three latent dimensions; then, we test a number of hypotheses to explain public opinion's support for each kind of sovereignist claim. Results show that some predictors, like conspiracy thinking, party-cueing, and political efficacy, are common to all three dimensions. Nonetheless, the use of media, left-right ideological orientations, and socio-demographic background do not have the same impact, thus confirming the theoretical distinction of these dimensions. Moreover, we find that populist parties can skilfully capitalize on people's grievances, by fostering sovereignist attitudes among their voters. However, the intrinsic heterogeneity of sovereignist supporters would make it difficult for one single movement to exploit the three dimensions and mobilize voters on all of them.